Tratamento termomecânico e higro-termomecânico de fibra de bucha vegetal para aplicação em compósitos com matriz cimentícia - Pires, Cristiane (2017)
This research investigates the thermomechanical and thermo-hygromechanical treatments of Luffa Cylindrica for reinforcement of the cementitious matrix, evaluating mechanical and physical properties and the durability of the composites. The treatments consist of hot pressing of fibers in dry condition (thermomechanical) or saturated condition (hygro- thermomechanical) and aim to improve the properties of the fibers reducing porosity and increasing mechanical properties. The fibers were pressed at room temperature, 120°C, 160°C and 200°C. After treatment, the fibers modulus of elasticity has improved and their moisture absorption has decreased. The saturated fibers pressed at temperature of 160 °C have presented no shape memory and their modulus of elasticity has increased 95% in relation to the fiber pressed at room temperature. However, the treated fiber surface became without roughness and impaired adherence with the matrix. To evaluate the performance in alkaline matrix, fiber reinforced cementitious composites were prepared of Luffa Cylindrica submitted to thermomechanical treatment at temperature of 160°C and reference fibers, pressed at room temperature. To reduce the alkalinity of the matrix, part of the cement was replaced by pozzolan. After previous studies of ideal contents, it was replaced 20% of cement by glass powder waste and 40% by tile ceramic waste. The results showed that the fibers pressed at 160°C exhibited good compatibility with the matrix, proven by increase of up to 70% on flexural strength and up to 80% on toughness of composites when comparing with reference samples. The analysis of X-ray diffractograms has shown that the replacement part of cement matrix by pozzolan reduced alkalinity, making less harmful to the fiber.